WALDRON ON CHARTERS OF RIGHTS: THE SCALES OF RESPECT - Grellette, Matthew (My University, 2006)
Jeremy Waldron condemns constitutional arrangements which attempt to incorporate democratic decision making together with a Charter of Rights and the attendant practice of judicial review. By playing on the fact of ubiquitous political disagreement among the members of any polit~, and by drawing upon a liberal value-set, Waldron asserts that the constitutional privileging of particular moral principles contained within a Charter of Rights must be seen to impinge upon the political respect which democratic decision making conveys unto I each member of a given polity. On this basis he contends that such mixed constitutional arrangements ought to be abandoned in favor of the purely democratic. The go~ of this thesis is to determine the soundness of this argument. Because it is evident that Waldron's critique would be successful given the conventional understanding of the nature and role of Charters of Rights, his argument is tested against a new conception of such constitutional mechanisms put forward by Wilfrid Waluchow. Although it is contended that Waluchow's position does not succeed in evading Waldron's claims concerning the democratic disrespect inherent in the adoption of a Charter of Rights, the nature of the investigation reveals the possibility of other manners in which such a constitutional mechanism does respect the citizenry of a state. On this basis it is contended that Waldron's arguments are invalid. More specifically, it is argued that it does not necessarily follow from the fact that Charters of Rights are in tension with pure democratic decision-making that they ought to be regarded as constitutionally undesirable.
Keywords: Philosophy; Philosophy